Sacral neuromodulation for the treatment of urinary bladder dysfunction: mechanism of action and future directions. Issue 1 (January 2018) - Blok, Bertil FM
Symptoms of overactive bladder affect a large portion of the world population, especially the elderly. Sacral neuromodulation (SNM) is an effective third-line therapy in patients with overactive bladder. The working mechanism of SNM can be explained by the neural connections of the lower urinary tract. It is proposed that SNM does not work directly on the central components of the micturition reflex, but on cortical and subcortical areas, which in turn inhibits the micturition reflex components in the caudal brainstem. The clinical use and outcomes of SNM are described for several forms of bladder dysfunction. Furthermore, some recent new developments in SNM are discussed, such as expanded indications, more effective use of existing nonrechargeable neuromodulators and the introduction of a rechargeable device.